Analysis Of Community Sentiment Towards The Implementation Of Zoning In New Student Admissions (PPDB) Using The Support Vector Machine (SVM) Algorithm - Rifai, Annas; Imelda, Imelda (Moneter: Jurnal Keuangan dan Perbankan, 2024)
Academic activities in each year have a routine agenda that must be implemented by educational institutions, especially schools, both public and private. Each level of schools competes to find interested applicants during the admission of new students (PPDB) starting from the level of kindergarten, elementary school, junior high school, and high school or equivalent. Every community that has children who will participate in PPDB is required to determine the most possible registration path, one of which is through the zoning path, where prospective students may register as PPDB participants provided that they have the closest distance to the school of interest based on the area zone. The zoning pathway is currently causing a polemic that is developing in the community, where the community feels that there is a mismatch in the application of this zoning policy, including many prospective students who have close proximity to schools but cannot register at the closest school from their domicile with various reasons submitted by the school, causing pros and cons. The purpose of this research is to analyze the value of community sentiment towards the application of zoning policies that apply to the new student registration system in each formal school. The data that will be used for data sentiment analysis are social media users, especially twitter. In this study using the SVM algorithm method where tweets from twitter users will be classified to produce positive and negative values. The result of the research is the classification of community sentiment in the form of positive and negative responses to the implementation of zoning so that it can be seen the current trend in society, if indeed more responses lead to negative responses, it means that it may be necessary to re-analyze whether this zoning registration path is appropriate or not.